Association between white matter fiber structure and reward‐related reactivity of the ventral striatum. Issue 4 (24th April 2013) - Koch, Kathrin; Wagner, Gerd; Schachtzabel, Claudia; Schultz, C. Christoph; Güllmar, Daniel; Reichenbach, Jürgen R.; Sauer, Heinrich; Zimmer, Claus; Schlösser, Ralf G.M.
<x xml:space="preserve">Abstract</x> Individual responsiveness to rewards or rewarding stimuli may affect various domains of normal as well as pathological behavior. The ventral striatum/nucleus accumbens (NAcc) constitutes a key brain structure in the regulation of reward‐appetitive behavior. It remains unclear, however, to which extent individual reward‐related BOLD response in the NAcc is dependent on individual characteristics of connecting white matter fiber tracts. Using tract‐based spatial statistics (TBSS) and statistical parametric mapping (SPM) this combined DTI ‐ fMRI study investigated this question by correlating NAcc BOLD signal upon receipt of a monetary reward with different white matter characteristics (FA, axial diffusivity, radial diffusivity). The results show that increased integrity of white matter as assessed by FA in the cingulate and corpus callosum, the inferior fronto‐occipital fasciculus, the anterior thalamic radiation and the anterior limb of the internal capsule was positively correlated with reward‐related activation in the NAcc. There were no negative correlations as well as no significant results regarding axial and radial diffusivity. These findings indicate that microstructural properties of fiber tracts connecting, amongst others, the cortex with the striatum may influence intensity of reward‐related responsiveness of the ventral striatum by constraining or increasing efficiency in information transfer within relevant circuitries involved in processing of reward. Hum Brain Mapp 35:1469–1476, 2014. © 2013 Wiley Periodicals, Inc.